Pelaksanaan Tugas Inspektur Kelaikudaraan Bidang Perawatan Pesawat Udara Dalam Menunjang Keselamatan Penerbangan Di Bandar Udara Internasional Sultan Hasanuddin Makassar - Kitty Claudia Salsa Bila Keibar; Elnia Frisnawati (Populer: Jurnal Penelitian Mahasiswa, 2023)
The Region V Airport Authority is one of the Technical Implementation Units (UPT) within the Ministry of Transportation which is responsible to the Minister of Transportation through the Directorate of Civil Aviation, where the duties of the airport authority itself are to supervise, control, and regulate activities both from the Land Side and Air Side at Sultan Hasanuddin International Airport Makassar. This research aims to find out (1) How is the implementation of the duties of the Airworthiness Inspector for Aircraft Maintenance in supporting flight safety at Sultan Hasanuddin International Airport Makassar, (2) What are the obstacles of Airworthiness Inspector for Aircraft Maintenance in carrying out duties at Sultan Hasanuddin International Airport Makassar. This research was conducted in February - March 2023 at the Makassar Region V Airport Authority Office, using descriptive research methods with qualitative analysis. Data collection was done through interview, observation, and documentation techniques. And Trigulation is used to test the reliability of the data obtained. The results of the discussion in this study are (1) in the implementation of the tasks carried out by the Airworthiness Inspector of the Aircraft Maintenance Division at Sultan Hasanuddin International Airport Makassar has carried out its duties properly in accordance with the regulations listed, one of which is PM 41 of 2011 and KP 252 of 2017, but not all tasks listed in the PM are carried out at the Region V Airport Authority because it must wait for delegation from the center first such as the Advanced Standard Certificate or can be called (CoA). (2) For the obstacles faced by inspectors at Sultan Hasanuddin International Airport Makassar, namely in the time and skills of the inspectors, where the inspectors cannot determine how long it takes when the inspection takes place because they have to see the ground time of the aircraft to be inspected and for human resources (Skil) inspectors at the Region V Airport Authority are lacking there are some inspectors who are still confused about analyzing the findings obtained.